2021
DOI: 10.3390/ijerph18115983
|View full text |Cite
|
Sign up to set email alerts
|

The Dark Triad Traits of Firefighters and Risk-Taking at Work. The Mediating Role of Altruism, Honesty, and Courage

Abstract: Firefighting is considered a dangerous profession that imposes unique safety hazards. In this research, we investigated the relationship between the Dark Triad traits of firefighters (N = 1434, Mage = 39.03, SD = 6.9) and their risk-taking at work, considering the mediation role of altruism, honesty, and courage. We showed that firefighters high on Machiavellianism and psychopathy reported high risk-taking. Altruism, honesty, and courage mediated the relationship between Machiavellianism and risk-taking in fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Rosca et al showed that these Dark Triad traits predicted risk-taking at work in firefighters, while altruism, honesty, and courage mediated the relationship between Machiavellianism and risk-taking. Honesty and courage mediated the relationship between psychopathy and risk-taking at work [68].…”
Section: Discussionmentioning
confidence: 96%
“…Rosca et al showed that these Dark Triad traits predicted risk-taking at work in firefighters, while altruism, honesty, and courage mediated the relationship between Machiavellianism and risk-taking. Honesty and courage mediated the relationship between psychopathy and risk-taking at work [68].…”
Section: Discussionmentioning
confidence: 96%
“…As hypothesized, the results demonstrate that dark traits tend to predict employees’ entitled outlooks which may bring numerous negative outcomes for the organizations. Individuals high on dark personality traits display a lack of empathy and caring about others, show a greater sense of selfishness and deservingness, and are less inclined to altruistic activities ( Roșca et al., 2021 ). Generally, individuals low on altruism are likely to engage more in unhelpful and non-cooperative behavior including knowledge hiding at the workplace.…”
Section: Discussionmentioning
confidence: 99%